The effects of war risk on US financial markets - Rigobon, Roberto; Sack, Brian (Journal of Banking & Finance, 2005)
This paper measures the effects of the risks associated with the war in Iraq on various US financial variables using a heteroskedasticity-based estimation technique. The results indicate that increases in war risk caused declines in Treasury yields and equity prices, a widening of lower-grade corporate spreads, a fall in the dollar, and a rise in oil prices. This “war risk” factor accounted for a considerable portion of the variances of these financial variables over the three months leading up to the arrival of coalition forces in central Baghdad.